Worst-case economics : extreme events in climate and finance - Ackerman, Frank (Anthem frontiers of global political economy., 2017)
In both climate change and financial crises, worst-case scenarios and disastrous risks are inescapable. Yet public policy often focuses on average or likely outcomes, minimizing the danger of extreme events. 'Worst-Case Economics: Extreme Events in Climate and Finance' explores the underlying causes and the remedies needed for the most serious climate and financial risks.